Acylated and Desacylated Ghrelin, Preptin, Leptin, and Nesfatin-1 Peptide Changes Related to the Body Mass Index. (25th November 2013) - Ozkan, Yusuf; Timurkan, Esra Suay; Aydin, Suleyman; Sahin, İbrahim; Timurkan, Mustafa; Citil, Cihan; Kalayci, Mehmet; Yilmaz, Musa; Aksoy, Aziz; Catak, Zekiye
Abstract : This study examines the levels of acylated and desacylated ghrelin, preptin, leptin, and nesfatin-1 peptide changes related to the body mass index (BMI). The subjects were allocated to 5 groups depending on their BMIs as follows: Group I (BMI <18.5 kg/m 2 ); Group II (BMI 18.5–24.9 kg/m 2 ); Group III (BMI 25–29.9 kg/m 2 ); Group IV (BMI 30–39.9 kg/m 2 ); Group V (BMI >40 kg/m 2 ). Serum acylated and desacylated ghrelin, preptin, and leptin levels were measured by the enzyme-linked immunosorbent assay (ELISA) and nesfatin-1 was measured by the enzyme immunoassay (EIA). Desacylated ghrelin levels showed a gradual and statistically significant drop from Group I to Group V, while preptin and leptin levels exhibited a gradual and significant increase from Group I to Group IV. Serum nesfatin-1 levels gradually, but not significantly, increased from Group I to Group III and showed a significant decrease in Groups IV and V. In conclusion, leptin, preptin, and acylated ghrelin (AG) levels increased with higher BMI, whereas desacylated ghrelin (DAG) decreased and nesfatin-1 showed no clear relationship to BMI.